“Ansiedad y elección profesional en los estudiantes de la Unidad Educativa “Combatientes de Tapi”. Riobamba. Octubre 2017-Marzo 2018”. - Maigua Moyota, Edith Paulina (2018)
Anxiety and professional choice are topics of great interest to students, teachers and parents, which is why the objective of this research was to determine the level of anxiety and its relationship with professional choice in third-year students of Bachillerato " A "and" D "of the Educational Unit" Tapi fighters ", the methodology had a non-experimental design, descriptive and correlational, for the time it was transversal, the population with the work was the students of the Educational Unit" Tapi Fighters ", the sample was non-probabilistic and intentional with 62 students, 13 women and 49 men from the third year of parallel baccalaureate" A "and" D ", the technique used was a Psychometric Test, the instrument was the GADI questionnaire, and part of the DECE the RGO test, through which the data was analyzed and interpreted, to reach the conclusion that the students present different anxiety levels but the most prevalent is the high level, which indicates that anxiety intervenes in professional choice since they have characteristics such as nervousness, insecurity, panic that affect when choosing a career.